Electroreduction of CO2 on Single‐Site Copper‐Nitrogen‐Doped Carbon Material: Selective Formation of Ethanol and Reversible Restructuration of the Metal Sites. (11th September 2019) - Karapinar, Dilan; Huan, Ngoc Tran; Ranjbar Sahraie, Nastaran; Li, Jingkun; Wakerley, David; Touati, Nadia; Zanna, Sandrine; Taverna, Dario; Galvão Tizei, Luiz Henrique; Zitolo, Andrea; Jaouen, Frédéric; Mougel, Victor; et al.
Abstract: It is generally believed that CO2 electroreduction to multi‐carbon products such as ethanol or ethylene may be catalyzed with significant yield only on metallic copper surfaces, implying large ensembles of copper atoms. Here, we report on an inexpensive Cu‐N‐C material prepared via a simple pyrolytic route that exclusively feature single copper atoms with a CuN4 coordination environment, atomically dispersed in a nitrogen‐doped conductive carbon matrix. This material achieves aqueous CO2 electroreduction to ethanol at a Faradaic yield of 55 % under optimized conditions (electrolyte: 0.1 m CsHCO3, potential: −1.2 V vs. RHE and gas‐phase recycling set up), as well as CO electroreduction to C2 ‐products (ethanol and ethylene) with a Faradaic yield of 80 %. During electrolysis the isolated sites transiently convert into metallic copper nanoparticles, as shown by operando XAS analysis, which are likely to be the catalytically active species. Remarkably, this process is reversible and the initial material is recovered intact after electrolysis. Abstract : N‐dotierter Kohlenstoff mit isolierten Cu‐Atomen erweist sich als hoch selektiv in der CO2 ‐Elektroreduktion zu Ethanol. Operando‐Spektroskopie des Katalysators zeigt, dass es sich bei der aktiven Spezies während der Elektrolyse um kurzlebige kleine Cu‐Nanopartikel handelt. Die Umstrukturierung der Metallzentren ist reversibel.